1995
DOI: 10.1007/bf01187524
|View full text |Cite
|
Sign up to set email alerts
|

Die t�gliche Kupfer-Aufnahme mit der Nahrung in Belgien, bestimmt aus doppelter Probenahme

Abstract: Daily dietary copper intake in Belgium has been evaluated by duplicate portion sampling, heating in a microwave oven and atomic absorption spectrometric determination of this element. The mean intake value (1.5 +/- 0.4 mg/day) is similar to levels found for most other countries, but is situated at the lower end of the recommended range for a safe and adequate daily dietary intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Duplicate diets of several population groups in Belgium (in the region of Antwerp) were analysed for Cu and Zn by atomic absorption spectrometry (Swerts et al 1993;Van Cauwenbergh et al 1995; Table 3).…”
Section: N T a K E D A T A F O R C O P P E R A N D Z I N Cmentioning
confidence: 99%
“…Duplicate diets of several population groups in Belgium (in the region of Antwerp) were analysed for Cu and Zn by atomic absorption spectrometry (Swerts et al 1993;Van Cauwenbergh et al 1995; Table 3).…”
Section: N T a K E D A T A F O R C O P P E R A N D Z I N Cmentioning
confidence: 99%
“…Many Polish and foreign authors reported various levels of Cu and Zn food de®ciency (Ellen et al 1990, Rutkowska et al 1991b, Buss and Rose 1992, Swerts et al 1993, Cauwenbergh et al 1995, Urieta et al 1996, Berry et al 1997, Ysart et al 1999. Recent data obtained by Szajkowski (1996) revealed a dramatically low daily intake of these trace elements with diet by seven groups of Wielkopolska Region inhabitants, which was close to half their safe levels.…”
Section: Resultsmentioning
confidence: 90%